Metagenomics: The Next Culture-Independent Game Changer - Forbes, Jessica D.; Knox, Natalie C.; Ronholm, Jennifer; Pagotto, Franco; Reimer, Aleisha (Frontiers in Microbiology, 2017)
A trend towards the abandonment of obtaining pure culture isolates in frontline laboratories is at a crossroads with the ability of public health agencies to perform their basic mandate of foodborne disease surveillance and response. The implementation of culture-independent diagnostic tests (CIDTs) including nucleic acid and antigen–based tests for acute gastroenteritis is leaving public health agencies without laboratory evidence to link clinical cases to each other and to food or environmental substances rendering the efficacy of point of care diagnostics, food safety, and identification of foodborne disease and antimicrobial resistance (AMR) in question. Foodborne outbreaks may have the potential to be undetected or have insufficient verification to resolve, and it is possible that this may inadvertently increase the incidence of foodborne disease. Next-generation sequencing on pure culture isolates in clinical microbiology laboratories has the potential to revolutionize the fields of food safety and public health. Metagenomics and other ‘omics’ disciplines could provide the solution to a cultureless future in clinical microbiology, food safety, and public health. Data mining of information obtained from metagenomics assays can be particularly useful for the identification of clinical causative agents or foodborne contamination, detection of AMR genes, provide high-resolution subtyping data, and to further understand mechanisms of virulence. Thus, metagenomics assays may provide a universal test for clinical diagnosis, foodborne pathogen detection, and subtyping. This information may help change the way we identify and handle foodborne pathogens. The aim of this review will be to present the current state of CIDTs in diagnostic laboratories as they relate to foodborne illness and food safety. Moreover, we will also discuss the diagnostic and subtyping utility and concomitant bias limitations of metagenomics and comparable detection techniques in clinical microbiology, food and public health laboratories. Early advances in the discipline of metagenomics, however, have indicated noteworthy challenges. Through forthcoming improvements, we anticipate that within the next decade, detection and characterization of pathogens via metagenomics-based workflows will be implemented in routine usage in diagnostic and public health laboratories.